Szkolnictwo chrześcijańskie w Polsce – sukces czy porażka? - Chyła (Kucharska), Anna Maria (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In this article I would like to present successes and failures of Christian schooling in Poland after 1989. My research was conducted in years 2013–2014 at ten schools located in different Polish towns and cities. Those schools are either strongly connected with Protestant churches or have an ecumenical Christian profile. At this stage of my research I am able to share and comment on the part of my results. For this paper I chose few quantitative and qualitative categories to present success and failure in their different meanings. I used data from schools websites as well as transcriptions of my interviews with school’s establishers and current headmasters. Main categories elaborated in this article are: number of schools, average exam results, community creation, individualisation in the educational process, changes of vision after establishing a school, financial support and relations with local authorities.
Keywords: protestantyzm; sukces edukacyjny; szkoły chrześcijańskie; wspólnota